Awareness and knowledge of sun exposure and use of sunscreen among adults in Aseer region, Saudi Arabia - Emad Bahashwan (Elsevier, 2024)
Background: Excessive sun exposure and inadequate sunscreen use can lead to skin cancer and other harmful effects on the skin, eyes, and immune system. Purpose: This observational cross-sectional study aimed to assess awareness and knowledge of sun exposure and sunscreen use among adults in the Aseer region, Saudi Arabia. This study also focused on evaluating the risks of skin cancer and participants' sun-protective attitudes and practices. Methods: A population-based cross-sectional study was conducted among adults in the Aseer region, Saudi Arabia. Data were collected using a questionnaire from November 2022 to January 2023 that assessed participants' knowledge, practices, and beliefs regarding sun exposure and sunscreen use. A total of 400 participants were selected for the study. Approval for the study was granted by the Local Research Ethics Committee of the University of Bisha, Saudi Arabia. Results: The results revealed that (59.8 %) of the participants were female, while (40.3 %) were male. Regarding age, the majority fell within the 26-35 age range (37.5 %), with (16.0 %) of participants using sunscreen regularly, with a total of (74.0 %) of participants using sunscreen. Men exhibited a higher prevalence of negative attitudes towards sun protection, while women demonstrated more favourable sun protection practices. In addition, (1.25 %) of the participants had skin cancer in the past; (81.0 %) of participants agreed that skin cancer could cause death, while (19.0 %) were unsure of the effects of skin cancer. Moreover, the results indicated that sun exposure had a significant positive effect on awareness levels (p < 0.05), indicating that increased sun exposure was associated with higher awareness of the harmful effects of the sun. Additionally, awareness level significantly positively affected sunscreen use (p < 0.01), suggesting that individuals with higher awareness were more likely to use sunscreen. Conclusion: There was an average awareness of sun exposure and its detrimental effects. In addition, a significant portion of the population demonstrates proactive measures to minimize sunlight exposure. However, sunscreen usage among Saudi adults was low despite having knowledge and awareness. Future research must enhance sun protection practices and reduce sun-related skin damage in the Aseer region.